Integrasi Sport Science dalam Kepelatihan Olahraga Prestasi: Studi Implementasi Evidence-Based Coaching pada Pelatih Kabupaten Jombang - Risfandi Setyawan; Ilmul Ma’arif; Guntum Budi Prasetyo (MAN Insan Cendekia Jambi, 2026)
The purpose of this study was to examine the implementation of sports science in high-performance sports coaching through an evidence-based coaching approach for coaches in Jombang Regency. This study used a qualitative approach with an implementation study design. The population of this study was sports coaches and the sample used a purposive sampling technique. Data collection was conducted through semi-structured interviews, non-participant observation, and document analysis. Data analysis used qualitative data with thematic analysis. Meanwhile, the results of the study showed that coaches have implemented the principles of sports science and evidence-based coaching in the planning, implementation, and evaluation of training programs. This approach has a positive impact on the consistency of athlete performance, physical and mental readiness, and achievement. However, obstacles were still found in the form of limited infrastructure, a lack of sports science support staff, and differences in coaches' abilities in interpreting scientific data. In conclusion, the integration of sports science through evidence-based coaching contributes to increasing the effectiveness of high-performance sports coaching, but requires systemic and sustainable support for optimal implementation.